2013
DOI: 10.1098/rsob.130073
|View full text |Cite
|
Sign up to set email alerts
|

A novel taxonomic marker that discriminates between morphologically complex actinomycetes

Abstract: In the era when large whole genome bacterial datasets are generated routinely, rapid and accurate molecular systematics is becoming increasingly important. However, 16S ribosomal RNA sequencing does not always offer sufficient resolution to discriminate between closely related genera. The SsgA-like proteins are developmental regulatory proteins in sporulating actinomycetes, whereby SsgB actively recruits FtsZ during sporulation-specific cell division. Here, we present a novel method to classify actinomycetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 66 publications
0
72
0
Order By: Relevance
“…A similar close relationship exists between Micromonospora, Verrucosispora, and Salinispora. Additional genetic markers have therefore been used to discriminate between closely related genera, including rpoB and, most recently, ssgB, which is particularly useful for discriminating between closely related genera (17). Moreover, the massive recent increase in the availability of genome sequence information has provided detailed insights into genome evolution and made it possible to identify genes specific to organisms at the level of genera and family (18).…”
Section: Taxonomy Of Actinobacteriamentioning
confidence: 99%
“…A similar close relationship exists between Micromonospora, Verrucosispora, and Salinispora. Additional genetic markers have therefore been used to discriminate between closely related genera, including rpoB and, most recently, ssgB, which is particularly useful for discriminating between closely related genera (17). Moreover, the massive recent increase in the availability of genome sequence information has provided detailed insights into genome evolution and made it possible to identify genes specific to organisms at the level of genera and family (18).…”
Section: Taxonomy Of Actinobacteriamentioning
confidence: 99%
“…We expect that the two strains are closely related kitasatosporae, a genus closely related to Streptomyces in the family of Streptomycetaceae. 41 This should be resolved by comparison of the genomes and phenotypic characteristics of the two strains. It is yet unclear which genes are responsible for the glycosylation of the endophenazine aglycones, as no such genes were found within or in close proximity of the epa gene cluster (Table 4).…”
Section: Identification Of Glycosylated Endophenazines C Wu Et Almentioning
confidence: 99%
“…This led to the identification of several streptomycetes that produce submerged spores, including Streptomyces granaticolor, S. griseus, Streptomyces roseosporus, and S. venezuelae (Daza, Martín, Dominguez, & Gil, 1989;Glazebrook, Doull, Stuttard, & Vining, 1990;Kendrick & Ensign, 1983). Although until recently it was believed that the ability to produce spores in liquid cultures was something like a rarity, the possibility cannot be ruled out that in principle all streptomycetes can do so under specific conditions; indeed, a recent survey revealed that submerged sporulation is likely much more widespread than originally anticipated, with half of a random selection of over 50 streptomycetes sporulating in submerged culture at least under some growth conditions (Girard et al, 2013). Although until recently it was believed that the ability to produce spores in liquid cultures was something like a rarity, the possibility cannot be ruled out that in principle all streptomycetes can do so under specific conditions; indeed, a recent survey revealed that submerged sporulation is likely much more widespread than originally anticipated, with half of a random selection of over 50 streptomycetes sporulating in submerged culture at least under some growth conditions (Girard et al, 2013).…”
Section: Submerged Sporulationmentioning
confidence: 99%
“…Homologues of SsgA-the SsgA-like proteins or SALPs-are found in all of what may be considered as morphologically complex actinomycetes, with a suggestive correlation between the number of SALPs and the number of spores produced per spore chain: species producing single spores (e.g., Micromonospora, Salinispora) typically have a single SALP, those producing short spore chains (e.g., Saccharopolyspora) typically have two SALPs, and those forming spore chains (Streptomyces) or sporangia (Frankia) have multiple SALPs (Girard et al, 2013;Traag & van Wezel, 2008). Homologues of SsgA-the SsgA-like proteins or SALPs-are found in all of what may be considered as morphologically complex actinomycetes, with a suggestive correlation between the number of SALPs and the number of spores produced per spore chain: species producing single spores (e.g., Micromonospora, Salinispora) typically have a single SALP, those producing short spore chains (e.g., Saccharopolyspora) typically have two SALPs, and those forming spore chains (Streptomyces) or sporangia (Frankia) have multiple SALPs (Girard et al, 2013;Traag & van Wezel, 2008).…”
Section: Ssga-like Proteins and Morphotaxonomy Of Actinomycetesmentioning
confidence: 99%